High temperature resistant reflective layer for wavelength conversion device

By forming a reflective layer composed of adhesive and reflective nanoparticles on the substrate of the wavelength conversion device, the problem of insufficient stability and durability of the reflective layer at high temperatures in the prior art is solved, and the effect of high reflectivity and long-term use is achieved.

CN119846891AActive Publication Date: 2025-04-18MATERION PRECISION OPTICS SHANGHAI LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510209249.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2019-04-19
Publication Date
2025-04-18
Estimated Expiration
2039-04-19

AI Technical Summary

Technical Problem

When the existing wavelength conversion device is used at high temperatures, the stability and durability of the reflective layer are insufficient, resulting in loss of optical performance and shortened service life.

Method used

Using a reflective layer composed of a binder and reflective nanoparticles, the binder may be organic or inorganic, with a particle size of about 200 nanometers to about 500 nanometers, a reflective layer formed on the substrate to improve light reflectivity and high temperature resistance.

Benefits of technology

Maintain the high stability and optical performance of the reflective layer at high temperatures (greater than 200°C), ensuring the service life of the wavelength conversion device and the long-term maintenance of reflectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119846891A_ABST
    Figure CN119846891A_ABST
Patent Text Reader

Abstract

A wavelength conversion device (100) includes a substrate (110), a reflective layer (120) on the substrate (110), and a wavelength conversion layer (130) on the reflective layer (120). The reflective layer (120) includes a binder (121) and reflective titanium dioxide nanoparticles (122). The nanoparticles (122) have a particle size of from about 200 nanometers to about 500 nanometers. The reflective layer (120) has enhanced thermal stability. Methods of making wavelength conversion devices are also disclosed herein.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with application number 2019800941612, application date April 19, 2019, and invention name “High temperature resistant reflective layer for wavelength conversion device”. Technical Field

[0002] The present disclosure relates to a wavelength conversion device such as a fluorescent wheel having a high temperature resistant reflective layer, and is therefore particularly suitable for a projection display system and an optical light conversion device using a solid-state laser as a light source. Background Art

[0003] A fluorescent wheel can be used to generate light of different wavelengths from a single light source. The fluorescent wheel comprises a circular substrate with surface segments of different colors. When the fluorescent wheel rotates with light (from the light source) incident on it, the surface segments convert the light into different wavelengths.

[0004] For a reflective fluorescent wheel, the substrate reflects light, so it is desirable to maximize the reflectivity of the substrate. For wavelengths from about 420 nm (nanometers) to about 680 nm, an aluminum (Al) coated substrate typically has an average reflectivity of 94%, while a silver (Ag) coated substrate has an average reflectivity of 98%.

[0005] However, stability and durability are also concerns for reflective wavelength conversion devices. After hundreds of hours of operation at high temperatures (greater than 150°C), burning phenomena in the laser incident area were observed on substrates coated with silver (Ag). The migration of silver ions in the coating at high temperatures may be the cause of this effect. Silver ion migration may cause a loss of optical performance of about 9%.

[0006] Silicones with high reflectivity (>95%) have been used to form the reflective layer of wavelength conversion devices. However, silicones have poor thermal stability. At temperatures above 200°C, silicones will degrade, typically starting to turn yellow and gradually begin to burn. At temperatures above 195°C, the phosphor layer on the reflective layer will also crack after about 1000 hours. Unexpectedly, the cracking of the phosphor layer results in a shortened service life of the phosphor wheel, and a sharp drop in light conversion efficiency due to thermal quenching has been observed (>10% at 200°C). In high brightness applications (e.g., 300W of laser power), the operating temperature of the phosphor wheel is typically expected to be above 200°C, so the use of silicone is not desirable.

[0007] It is desirable to have a substrate with high reflectivity throughout its service life. It is also desirable to increase substrate reflectivity at a low cost while maintaining and increasing reliable service life performance. Such substrates and reflective coatings / layers can be advantageously used in a variety of applications, such as light tunnels, projection display systems, and optical light conversion devices such as phosphor wheels used in such systems. Summary of the invention

[0008] The present disclosure relates to compositions for forming reflective layers in wavelength conversion devices such as fluorescent wheels or color wheels; reflective layers containing certain materials; and wavelength conversion devices containing such reflective layers. Such reflective layers resist temperature degradation at high operating temperatures (e.g., greater than 200° C. or even up to 250° C.). Methods of making and using such compositions, layers, and devices are also disclosed herein.

[0009] Various embodiments herein disclose a wavelength conversion device, comprising: a substrate; a reflective layer on the substrate; and a wavelength conversion layer on the reflective layer. The reflective layer comprises a binder (A); and reflective nanoparticles (B), the reflective nanoparticles having a particle size of about 200 nanometers to about 500 nanometers.

[0010] In some embodiments, the reflective nanoparticles are pure titanium dioxide (TiO2), or aluminum oxide (Al2O3), or magnesium oxide (MgO). In other embodiments, the reflective nanoparticles are titanium dioxide (TiO2) surface-modified with organic alcohols, siloxanes, aluminum oxide (Al2O3), zirconium dioxide (ZrO2) or silicon dioxide (SiO2).

[0011] The reflective layer may have a thickness of about 0.05 mm to about 0.15 mm. A weight ratio of the reflective nanoparticles (B) to the binder (A) may be about 1:2.5 to about 1:0.8.

[0012] The binder may be an organic binder or an inorganic binder. Examples of organic binders include organic silicon such as octamethyltrisiloxane, etc. Examples of inorganic binders include sodium silicate.

[0013] It is desirable that the reflective layer has a reflectivity of at least 95% for light having a wavelength of about 420 nm to about 680 nm. The phosphor layer may include phosphor particles dispersed in glass, or in a crystal, or in a ceramic material. The substrate may have a disc shape. The wavelength converter may also include a motor for rotating the substrate. The substrate may be of a metal or non-metal material or a composite material.

[0014] Also disclosed herein is a light projection system comprising the wavelength conversion device described herein.

[0015] Also disclosed in various embodiments is a method for manufacturing a wavelength conversion device, the method comprising: applying a composition to a substrate to form a reflective layer on the substrate, the composition comprising a binder (A); and reflective nanoparticles (B) having a particle size of about 200 nanometers to about 500 nanometers; and forming a wavelength conversion layer on the reflective layer.

[0016] When applied to a substrate, the composition may have a viscosity of about 0 centipoise (cP) to about 1500 centipoise (cP). The method may further include curing the composition at a temperature of about 85° C. to about 150° C. The composition may be applied by dispensing, spraying, brushing, flowing, coating, or screen printing.

[0017] These and other non-limiting features of the present disclosure are more particularly disclosed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The following is a brief description of the accompanying drawings for illustrating exemplary embodiments disclosed herein, rather than for the purpose of limiting the present disclosure.

[0019] Figure 1A is a schematic diagram of an exemplary optical light conversion device according to the present disclosure, the device including a substrate, a high reflectivity layer, and a phosphor layer.

[0020] Figure 1B yes Figure 1A A side cross-sectional view of an exemplary optical light conversion device.

[0021] Figure 1C is an exploded view of the layers of an optical light conversion device.

[0022] Figure 2A is a graph showing the relationship between the reflectivity and the thickness of the reflective layer of the first fluorescent wheel of the present disclosure.

[0023] Figure 2B is a graph showing the relationship between the reflectivity and the thickness of the reflective layer of the second fluorescent wheel of the present disclosure. DETAILED DESCRIPTION

[0024] A more complete understanding of the components, methods, and devices disclosed herein may be obtained by referring to the accompanying drawings, which are merely schematic diagrams for convenience and ease of illustrating the present disclosure and are therefore not intended to indicate the relative size and dimensions of the device or its components and / or to define or limit the scope of the exemplary embodiments.

[0025] Although specific terms are used in the following description for the sake of clarity, these terms are intended only to refer to the specific structures of the embodiments selected for illustration in the drawings, and are not intended to define or limit the scope of the present disclosure. In the drawings and the following description, it should be understood that the same reference numerals represent components with the same functions.

[0026] The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0027] As used in the specification and claims, the terms "comprising," "including," "having," "can," "containing," and variations thereof as used herein are intended to be open-ended transitional phrases, terms, or words that require the presence of specified ingredients / steps and allow for the presence of other ingredients / steps. However, such descriptions should be interpreted as also describing compositions or methods as "consisting of the listed ingredients / steps" and "consisting essentially of the listed ingredients / steps," which allow for the presence of only the named ingredients / steps, along with any unavoidable impurities that may result therefrom, and exclude other ingredients / steps.

[0028] Numerical values ​​in the specification and claims of this application should be understood to include values ​​that are the same when reduced to the same number of significant figures and values ​​that differ from the stated value by less than the experimental error of routine measurement techniques of the type described in this application used to determine the value.

[0029] All ranges disclosed herein include the recited endpoints and independently combinable intermediate values ​​(eg, the range of "2 grams to 10 grams" includes the endpoints 2 grams and 10 grams, and all intermediate values).

[0030] The terms "about" and "approximately" can be used to include any numerical value that can vary without changing the basic function of the value. When used with a range, "about" and "approximately" also disclose the range defined by the absolute values ​​of the two endpoints, for example, "about 2 to about 4" also discloses the range "2 to 4". In general, the terms "about" and "approximately" can refer to the specified number plus or minus 10%.

[0031] As used herein, the terms "excitation light" and "excitation wavelength" refer to input light that is subsequently converted, such as light produced by a laser-based illumination source or other light source. The terms "emission light" and "emission wavelength" refer to converted light, such as synthetic light produced by a phosphor that has been exposed to the excitation light.

[0032] As used herein, the term "inorganic" refers to an "inorganic" object that does not contain any carbon. For the avoidance of doubt, the terms "inorganic binder" and "inorganic coating" of the present disclosure do not include carbon.

[0033] For reference, red generally refers to light with a wavelength of about 780 nanometers to about 622 nanometers. Green generally refers to light with a wavelength of about 577 nanometers to about 492 nanometers. Blue generally refers to light with a wavelength of about 492 nanometers to about 455 nanometers. Yellow generally refers to light with a wavelength of about 597 nanometers to about 577 nanometers. However, this may depend on the context. For example, these colors are sometimes used to mark various components and distinguish these components from each other.

[0034] The present disclosure relates to a wavelength conversion device including a reflective layer having a specific composition. Specifically, the reflective layer includes a binder (A), which can be organic or inorganic; and reflective nanoparticles (B), the reflective nanoparticles having a particle size of about 200 nanometers to about 500 nanometers (including about 350 nanometers to about 450 nanometers). These reflective layers will work at high temperatures (e.g., greater than 200°C or 250°C) while maintaining other optical and mechanical parameters such as total reflectivity percentage.

[0035] Whether the reflective layer maintains high stability can be determined by either of two methods. In the first method, a fluorescent wheel using a reflective layer is placed in an oven and the fluorescent wheel is aged at 250°C. The reflectivity is tested every 100 hours, at least for 500 hours, and the reflective layer is observed to see if there are any cracks. If the reflectivity measured between the 300th, 400th, and 500th hours changes by less than 2%, and there are no cracks in the reflective layer, the reflective layer is considered to maintain high stability. In the other method, a fluorescent wheel using a reflective layer is placed in an oven and the fluorescent wheel is aged at 250°C. The conversion efficiency is tested every 100 hours, at least for 500 hours, and the reflective layer is observed to see if there are any cracks. If the conversion efficiency measured between the 300th, 400th, and 500th hours changes by less than 2%, and there are no cracks in the reflective layer, the reflective layer is considered to maintain high stability. The reflective layer can be considered to maintain high stability by only one of these two methods.

[0036] See also Figure 1A and Figure 1B , which depicts a wavelength conversion device of the present disclosure. The wavelength conversion device is shown in the form of a fluorescent wheel 100. Figure 1A is a schematic diagram of the fluorescent wheel 100, Figure 1B 1 is a side cross-sectional view of a fluorescent wheel 100. The fluorescent wheel 100 includes a substrate 110 having a reflective layer 120 formed thereon, wherein a phosphor layer 130 is applied to the reflective layer 120. The reflective layer is formed from a composition further described herein. As shown here, the reflective layer 120 is formed from an inorganic binder or silicone (A) labeled with reference numeral 121 and reflective nanoparticles labeled with reference numeral 122.

[0037] The substrate 110 is generally a metal with high thermal conductivity, such as aluminum or aluminum alloy, copper or copper alloy, silver or silver alloy, or other metal with high thermal conductivity. For example, the substrate can also be made of non-metallic materials or composite materials such as glass, sapphire or diamond. The substrate is generally disc-shaped or annular. The smoothness or roughness of the substrate surface is not important. However, it is desirable that the surface of the substrate formed with the reflective layer 120 is clean and there is no stain, oil, organic residue or biological residue on the substrate. For low surface energy surfaces, adhesion can be improved by applying a primer or by special surface treatment (such as chemical or plasma etching or ozone cleaning).

[0038] The phosphor layer 130 includes at least one phosphor. Examples of suitable phosphors include yttrium aluminum garnet (YAG), silicates, and nitrides. The phosphor may have a particle size of about 10 to about 30 microns. The phosphor layer is typically in the form of annular phosphor segments that include different types of phosphors to convert the excitation light into green, yellow, or red light. Typically, a blue laser (having a wavelength of about 440 nm to about 460 nm) is used to excite the phosphor segments on the phosphor wheel. The phosphor wheel may also have one or more gaps to allow the blue source light to pass through without conversion.

[0039] Can be used by mounting the base plate on a motor to rotate at high speed Figure 1A and Figure 1B Typically, the substrate is caused to rotate during use, although the device may also be used in a static (non-rotating) configuration, in which case the device may not be referred to as a fluorescent wheel. Figure 1A The rotation of the fluorescent wheel is depicted in FIG. 1 by an arrow rotating about an axis AA which passes through the substrate 110 and is perpendicular to the planar surface of the substrate 110. Thus, light of different wavelengths is sequentially generated.

[0040] like Figure 1A and Figure 1BAs shown, excitation light 123 (i.e., excitation light or input light) having an excitation wavelength from a light source (not shown) (e.g., a laser-based illumination source) is focused on the phosphor layer. Emission light 124 (i.e., emission light or converted light) having an emission wavelength is generated by the phosphor layer. In this way, the phosphor layer converts the spectrum of the excitation light from the first spectral wavelength range into emission light (or re-emission) of the second spectral wavelength range, and the first spectral wavelength range and the second spectral wavelength range have different spectral wavelength ranges. When light with an excitation wavelength 123 (e.g., a laser beam blue light) is focused on the phosphor layer, light with an emission wavelength 124 (e.g., yellow light) will be emitted in all directions (including toward the substrate). The reflective layer 120 is used to reflect and redirect the emission light away from the substrate so that the light is emitted on the same side of the substrate as the side receiving the excitation light. The emission light can be collected (e.g., by a lens) and used for subsequent downstream processes.

[0041] The reflective layer 120 includes a binder (A), which may be organic or inorganic; and reflective nanoparticles (B) having a particle size of about 200 nanometers to about 500 nanometers. In a more specific embodiment, the reflective nanoparticles have a particle size of about 350 nanometers to about 450 nanometers.

[0042] For the adhesive (A), suitable materials should work for a long time (at least 20,000 hours) in a temperature range of -45°C to 250°C (-49°F to +482°F). It is desirable that the adhesive can work for a long time at a temperature above 200°C. The adhesive (A) can be an organic adhesive or an inorganic adhesive.

[0043] An example of an organic binder is a silicone, such as octamethyltrisiloxane, a reflective resin. Such silicones are commercially available from Dow or Sumitomo Chemical. Prior to coating, the silicone may be mixed with an organic solvent, which may include methylsiloxane. An example of an organic solvent is OS-20 sold by Dow Corning Corporation, which is a volatile solvent used as a diluent to adjust the viscosity of the solution. The mixed silicone / solvent is uniformly prepared according to the process requirements, and a silicone oil diluent may be added to adjust the viscosity before being put into the mixer for mixing.

[0044] Alternatively, the binder (A) may be an inorganic binder having certain properties. It is desirable that the inorganic binder has a coefficient of thermal expansion (CTE) of about 0.5 to about 25 ppm / °C. In a specific embodiment, the inorganic binder is sodium silicate. Sodium silicate is of the formula (Na2SiO3) n The common name of the compound, which can also be considered a polymer, is shown in the following formula (I).

[0045]

[0046] Sodium silicate has an anhydrous form and a hydrated form Na2SiO3·nH2O, where n=5, 6, 8 or 9. The characteristics of sodium silicate can be expressed by the weight ratio of silicon dioxide (SiO2) to sodium oxide (Na2O). SiO2:Na2O can vary from 2:1 to 3.75:1. In specific embodiments, SiO2:Na2O can be from about 2.5:1 to about 3.75:1, or from about 2:1 to about 3:1. Sodium silicate is generally provided in the form of an aqueous solution.

[0047] In other embodiments, the inorganic binder may be made of other inorganic materials besides sodium silicate. These inorganic materials may be silicates, aluminates, phosphates, borates, or inorganic sol-gels. Examples of inorganic sol-gels include sol-gels made of silicon dioxide (SiO2) or aluminum oxide (Al2O3).

[0048] In another exemplary embodiment, the inorganic binder is formed from a first component and a second component. The total dissolved solids (TDS) properties of the inorganic binder used are provided in the following table:

[0049]

[0050] This particular inorganic adhesive is prepared by mixing a first component and a second component and stirring for about 2 to about 3 hours at a temperature of about 25 to about 30° C. The ratio of the first component to the second component is from about 1:1 to about 7:3.

[0051] It is desirable that the inorganic binder (A) is substantially optically transparent (e.g., the inorganic binder has a light transmittance of at least 80%, including 90% and up to 98%). For example, as measured using a spectrophotometer available from Idea Optics with a thickness of about 0.1 to about 0.2 mm. In contrast, many inorganic binders are opaque.

[0052] In specific embodiments, the inorganic adhesive of the present disclosure is resistant to high temperatures (e.g., temperatures greater than 200°C, including 300°C or higher, or up to 400°C), has high light transmittance (e.g., at least 98%), has high tensile shear strength (e.g., at least 100 psi at 300°C), can be applied by a flexible coating process (e.g., dispersing, screen printing, spraying), and has a low curing temperature (e.g., less than 185°C).

[0053] The reflective layer also contains reflective nanoparticles (B). It is believed that the presence of the reflective nanoparticles reduces the shrinkage of the adhesive (A), thereby reducing the formation of cracks and bubbles. Stress during assembly is thereby avoided and the bonding strength of the reflective layer to the substrate is improved. Ideally, the thermal expansion coefficient of the reflective nanoparticles should be as close as possible to that of the adhesive (A), and their densities should also be as close as possible to avoid delamination of the components.

[0054] The reflective nanoparticles have a particle size of about 200 nanometers to about 500 nanometers (including about 300 nanometers to about 500 nanometers and about 350 nanometers to about 450 nanometers). The reflective nanoparticles can be made of pure titanium dioxide (TiO2) or modified TiO2. The modified TiO2 nanoparticles can be surface-modified with organic alcohols, siloxanes, aluminum oxide (Al2O3), zirconium dioxide (ZrO2) or silicon dioxide (TiO2). In a preferred embodiment, the reflective nanoparticles are pure TiO2.

[0055] The weight ratio of the reflective nanoparticles to the (A) binder may be from about 1:2.5 to about 1:0.8 (including from about 1:2 to about 1:1). The reflective nanoparticles (B) should be mixed with the binder (A) and then the mixture refrigerated before use. For example, the nanoparticles can be mixed with the binder twice, each time at 800 rpm for about 2 minutes, before refrigeration at about 4°C for about 24 hours. It is desirable that the reflective nanoparticles are uniformly dispersed throughout the mixture so that the reflective nanoparticles are also uniformly dispersed throughout the reflective layer.

[0056] The reflective layer can be formed by applying a mixture of a binder (A) and reflective nanoparticles (B) to a substrate. The mixture can be applied by dispersing, spraying, brushing, flowing, pattern coating or screen printing.

[0057] In applications where the mixture is applied by dispersion or screen printing, the mixture should have a suitable viscosity of about 0 to about 1,500 centipoise (cP) (including about 100 cP to about 800 cP, or about 100 cP to about 600 cP, or about 200 to about 500 cP, or about 1,000 cP to about 1,500 cP). The viscosity is measured using a Brookfield DVE SLVTJO viscometer or according to ASTM D1084. The inorganic binder itself (i.e., without TiO2 nanoparticles) may also have a suitable viscosity of about 0 to about 1,500 centipoise (cP) (including about 0 to about 800 cP, or about 100 cP to about 800 cP).

[0058] In some cases, it is expected that the reflective layer will be constructed over multiple application rounds. For example, in the first round, the mixture of the adhesive (A) and the reflective nanoparticles (B) is stirred, and the mixture is then sprayed onto the substrate to form a reflective layer having a thickness of about 0.025 mm to about 0.075 mm. The first layer is then allowed to stand at room temperature for about 0.5 hours, and then the first layer is cured at a temperature of about 85°C for about 0.5 hours. In the second round, the mixture of the adhesive (A) and the reflective nanoparticles (B) is stirred again, and then the mixture is sprayed onto the first layer, and then allowed to stand at room temperature for about 0.5 hours, and then cured at a temperature of about 85°C for about 0.5 hours. The above steps result in the reflective layer having a total thickness of about 0.05 mm to about 0.15 mm.

[0059] Desirably, the reflective layer is configured to reflect within a wavelength range of about 380 nm to about 800 nm, more preferably configured to reflect within a wavelength range of about 420 nm to about 680 nm. The reflectivity of the reflective resin layer is generally at least (or greater than) 90%, and more preferably at least (or greater than) 94%, or 95%, or 96%, or 97%, or 98%, or 99%.

[0060] The reflective layer may have a total thickness of about 0.05 mm to about 0.15 mm. In a specific embodiment, the reflective layer has a thickness of about 0.07 mm to about 0.12 mm. The thickness is set to maximize the reflectivity of the light output in the desired wavelength range. Thicker layers provide higher reflectivity, but may also cause long-term failures, such as due to peeling or cracking of the reflective layer. Therefore, the optimal thickness can be determined by the optimal reflectivity and / or a certain compromise between reflectivity and durability.

[0061] The reflective layer is typically distinguished (and distinguishable) from the phosphor layer by its composition and / or structure. In particular, the reflective layer is typically significantly more reflective than the phosphor layer. The phosphor layer is typically not reflective. Typically, the reflective layer does not include a wavelength conversion material (e.g., phosphor).

[0062] The reflective layer containing reflective nanoparticles disclosed herein can maintain a total reflectivity of at least 95% at a temperature above 200°C. The reflective layer can be cured at a relatively low temperature of 85°C to 150°C. The reflective layer shows reliable operation at high laser irradiance and temperature. The reflective layer can also be flexibly made into various sizes, shapes and thicknesses. The reflective layer can also withstand high operating temperatures, i.e., operating temperatures exceeding 200°C, up to 250°C. The reflective layer can be used in high-power laser projection display systems, in which a solid-state laser projector can be equipped with a laser power of about 60 watts to about 300 watts (including more than 100 watts). The operating temperature of such a device can reach above 200°C, thereby having a high luminous brightness.

[0063] In some embodiments, the reflective layer 120 may also serve as a bonding layer between the substrate 110 and the phosphor layer 130. Alternatively or additionally, an auxiliary bonding layer (e.g., glue or tape) may also be used to adhere the phosphor layer to the reflective layer. This is useful for certain solid phosphor layers made of phosphor particles dispersed in, for example, glass, crystal, or ceramic materials.

[0064] Return to reference Figure 1A and Figure 1C , it can be noted that the width of the reflective layer 120 (measured in the radial direction on the substrate) can vary. Figure 1A In the embodiment, the width of the reflective layer 120 is much larger than the width of the phosphor layer 130. Figure 1C As shown, the width of the reflective layer 120 may also be substantially equal to the width of the phosphor layer 130. Typically, the width of the reflective layer 120 is at least equal to the width of the phosphor layer 130, and may be greater than the width of the phosphor layer.

[0065] It is contemplated that the reflective layers described herein may be used in fluorescent wheels and laser projection display systems. They may also be used in conjunction with solid-state lighting sources (e.g., automotive headlights).

[0066] The following examples are used to illustrate the methods of the present disclosure. The examples are illustrative only and are not intended to limit the present disclosure to the materials, conditions or process parameters described herein.

[0067] Example

[0068] Example 1

[0069] Two fluorescent wheels with a reflective layer composed of an inorganic binder and TiO2 nanoparticles were manufactured. The inorganic binder of the reflective layer was formed from a first component and a second component. The total dissolved solids (TDS) properties of the inorganic binder are provided in the following table:

[0070]

[0071] The weight ratio of inorganic binder to TiO2 nanoparticles is 1:1.7. The first fluorescent wheel, labeled PT01, uses TiO2 nanoparticles with a particle size of 0.4-0.45 μm (i.e., 400-450 nm). The second fluorescent wheel, labeled PT02, uses TiO2 nanoparticles with a particle size of 0.36 μm (i.e., 360 nm).

[0072] The inorganic binder and the TiO2 nanoparticles were mixed in a mixer twice, each time at 800 rpm for two minutes, to prepare an inorganic scattering layer material (ISLM).

[0073] Interestingly, ISLM behaves as a shear-thinning fluid, i.e., its viscosity decreases when stirred. PT02 powder also tends to clump, resulting in incomplete absorption of the glue. Therefore, ISLM was placed in a 4°C refrigerator for 24 hours to ensure that the inorganic binder was completely absorbed by the PT02 powder. After 24 hours, ISLM was gently stirred by hand to ensure that the mixed material was uniform. The viscosity of ISLM was 1000-1500 centipoise (cP).

[0074] ISLM was applied using an automatic sprayer (PVA350). The spraying air pressure was adjusted to 3.5 MPa. ISLM was sprayed twice on an Al (aluminum) plate to obtain a wet reflective layer. The wet reflective layer was left at room temperature for 0.5 hours and cured at 85°F for 0.5 hours to obtain a reflective layer with a thickness of 0.045 mm. A second layer was applied on top of the first layer to obtain a reflective layer with a total thickness of 0.09 mm. The reflective layer was cured at 185°F for 0.5 hours to ensure that the reflective layer was fully cured.

[0075] First, the diffuse reflectance of the PT01 and PT02 phosphor wheels was measured at different reflective layer thicknesses. Figure 2A The results of the PT01 fluorescence wheel are shown in Table A below. Figure 2B The results for the PT02 phosphor wheel are shown in Table B below. From these results, it can be seen that the reflectivity is stable at greater than 94% at a thickness of 0.08 mm (PT01) or 0.07 mm (PT02).

[0076] Table A.PT01

[0077] Thickness(mm) Diffuse reflectivity (%) 0.02 84.2 0.02 90.6 0.04 92.6 0.08 94.2 0.09 94.7 0.09 94.4 0.10 94.5

[0078] Table B.PT02

[0079] Thickness(mm) Diffuse reflectivity (%) 0.050 93.0 0.070 94.5 0.075 94.5 0.080 94.4 0.082 94.8 0.093 94.6

[0080] Next, the two fluorescent wheels PT01 and PT02 were compared with two other fluorescent wheels. The first control wheel, labeled G1, used only inorganic binders in the reflective layer (i.e., no TiO2 nanoparticles). The second control wheel, labeled G1.5, used only organic binders in the reflective layer (no TiO2 nanoparticles).

[0081] Output power tests were performed at different thicknesses to compare the PT02 fluorescence wheel and the G1 fluorescence wheel. The results for the PT02 fluorescence wheel are shown in Table C, and in the last column, 100% of the results were obtained with the G1 fluorescence wheel.

[0082] Table C

[0083] Thickness(mm) Diffuse reflectivity (%) Output power 100W % of G1 0.07 94.7 48.0 106.3 0.08 94.7 48.2 106.6 0.09 94.6 48.0 106.2

[0084] Next, reliability testing was performed to compare the PT02 fluorescent wheel and the G1 fluorescent wheel at 100 W and 50 W. The test conditions are shown in Table D. Three samples were run for each test. The results for the PT02 fluorescent wheel are shown in Table E. Again, 100% of the results were obtained with the G1 fluorescent wheel.

[0085] Table D

[0086]

[0087] Table E

[0088] Input Power Thermal shock High humidity % of G1 output power 100W 106.2% 105.9% 106.3% 50W 106.1% 106.1% 106.2%

[0089] Finally, the PT02 phosphor wheel and the G1 phosphor wheel were compared at 100 W and 50 W. The samples were placed in a muffle furnace at 250°C and the output performance was tested over time. The results for the PT02 phosphor wheel are shown in Table F. Again, 100% of the results were obtained with the G1 phosphor wheel. The results show that the PT02 phosphor wheel is stable and no cracks are generated between the reflective layer and the phosphor layer.

[0090] Table F

[0091] Time (hours) 100W 50W 0 106.3% 106.2% 115 105.9% 106.0% 206 106.3% 105.8% 349 106.1% 106.1% 513 106.0% 105.9%

[0092] Output power tests were performed at different thicknesses to compare the PT01 and G1 fluorescence wheels. The results for the PT01 wheel are shown in Table G, and in the last column, 100% of the results were obtained with the G1 fluorescence wheel.

[0093] Table G

[0094]

[0095] Next, reliability testing was performed to compare the PT01 fluorescent wheel and the G1 fluorescent wheel at 100 W and 50 W. The test conditions are shown in Table D above. Three samples were run for each test. The results for the PT01 fluorescent wheel are shown in Table H. Again, 100% of the results were obtained with the G1 fluorescent wheel.

[0096] Table H

[0097] Input Power Thermal shock High humidity Low temperature Output power of G1 % 100W 106.0% 106.1% 106.3% 106.4% 50W 106.0% 105.5% 106.3% 106.1%

[0098] Finally, the PT01 phosphor wheel and the G1 phosphor wheel were compared at 100 W and 50 W. The samples were placed in a muffle furnace at 250°C and the output performance was tested over time. The results for the PT01 phosphor wheel are shown in Table I. Again, 100% of the results were obtained with the G1 phosphor wheel. The results show that the PT01 phosphor wheel is stable and no cracks are generated between the reflective layer and the phosphor layer.

[0099] Table I .

[0100] Time (hours) 100W 50W 0 106.2% 106.3% 230 106.1% 106.1% 350 106.1% 106.1% 500 105.4% 106.1%

[0101] Example 2

[0102] Diffusion tests were performed with different types of nanoparticles: TiO2, Al2O3, and Al. The binder was an inorganic binder. Layers of varying thickness were prepared and tested for diffusivity (i.e., diffuse reflectivity). Table J describes five different mixtures, and Table K provides the diffusivity results for three mixtures. It may be noted that since the mixtures were sprayed manually, a given layer may have varying thicknesses.

[0103] Table J

[0104]

[0105] Table K

[0106] mixture# Layer thickness (mm) Diffusion rate (%) 2 0.05-0.07 84-86,89,89 2 0.06-0.08 89-90 2 0.08-0.09 89.5 2 >0.08 90-92 2 >0.1 88.9 3 0.1-0.15 76-86 3 0.13-0.18 91-92 3 0.2-0.3 87-89 3 >0.2 88 4 0.05-0.07 89-90 4 0.09 91-92 4 >0.1 92-96 4 0.15-0.17 86-94 4 0.18 94 4 0.15-0.2 89-94 4 0.2 95.9 4 >0.2 94-97

[0107] The results in Table K show that the diffusion rate of Al2O3 nanoparticles exceeds 94% when the layer thickness exceeds 0.15 mm. However, the reflectivity of Al2O3 is unstable (i.e., varies greatly) and requires a thickness of Al2O3 that is greater than the thickness of TiO2 nanoparticles with the same reflectivity. Al2O3 is also prone to cracking. Therefore, it is concluded that TiO2 is the best nanoparticle for high reflectivity layers.

[0108] Example 3

[0109] Diffusion rate tests were performed using different TiO2 nanoparticles from different suppliers as well as Al(OH)3 and MgO. The binder was an inorganic binder. Layers of different thicknesses were prepared and tested for diffusion rate. Table L describes six different mixtures and Table M provides the diffusion rate results for five mixtures. It can be noted that the MgO particles are large and cannot be mixed uniformly.

[0110] Table L

[0111]

[0112] Table M.

[0113]

[0114] Mixture #5 can achieve a diffusivity greater than 94%. The results also show that diffuse reflectivity greater than 90% can be achieved using 0.2 μm and 0.5 μm TiO2 nanoparticles.

[0115] The content of the present disclosure has been described with reference to the preferred embodiment. After reading and understanding the above detailed description, others may think of modifications and changes. As long as the above modifications fall within the scope of the attached claims or their equivalents, the present disclosure is interpreted as including all the above-mentioned types of modifications and changes.

Claims

1. A wavelength conversion device, comprising: substrate; A reflective layer on the substrate, the reflective layer comprising: Binder (A), wherein the binder (A) is an inorganic binder comprising an inorganic sol-gel made of silica or alumina; and Reflective titanium dioxide (TiO2) nanoparticles (B), the reflective titanium dioxide (TiO2) nanoparticles (B) are surface-modified with organic alcohol, siloxane, aluminum oxide (Al2O3), zirconium dioxide (ZrO2) or silicon dioxide (SiO2), and the reflective titanium dioxide (TiO2) nanoparticles (B) have a particle size of 200 to 500 nanometers, wherein the weight ratio of the reflective titanium dioxide (TiO2) nanoparticles (B) to the binder (A) is from 1:2 to 1:1; and a wavelength conversion layer on the reflective layer; Wherein, the reflective layer is thermally stable at a working temperature of 250°C.

2. The wavelength conversion device according to claim 1, wherein: The reflective layer has a thickness of 0.05 mm to 0.15 mm.

3. The wavelength conversion device according to claim 1, wherein: The reflective titanium dioxide (TiO2) nanoparticles (B) have a particle size of 350 nm to 450 nm.

4. The wavelength conversion device according to claim 1, wherein: The reflective layer has a reflectivity of at least 95% with respect to light having a wavelength of 420 nm to 680 nm.

5. The wavelength conversion device according to claim 1, wherein: The wavelength conversion layer is a phosphor layer, and the phosphor layer includes phosphor particles dispersed in glass, crystal, or ceramic material.

6. The wavelength conversion device according to claim 1, wherein: The substrate has a disc shape.

7. The wavelength conversion device according to claim 1, further comprising a motor for rotating the substrate.

8. The wavelength conversion device according to claim 1, wherein: The substrate is made of metal, non-metal or composite material.

9. A light projection system, comprising the wavelength conversion device according to claim 1.

10. A method for manufacturing a wavelength conversion device, the method comprising: A composition is applied to a substrate to form a reflective layer on the substrate, the composition comprising: Binder (A), wherein the binder (A) is an inorganic binder comprising an inorganic sol-gel made of silica or alumina; and Reflective titanium dioxide (TiO2) nanoparticles (B), the reflective titanium dioxide (TiO2) nanoparticles (B) are surface-modified with organic alcohol, siloxane, aluminum oxide (Al2O3), zirconium dioxide (ZrO2) or silicon dioxide (SiO2), and the reflective titanium dioxide (TiO2) nanoparticles (B) have a particle size of 200 to 500 nanometers, wherein the weight ratio of the reflective titanium dioxide (TiO2) nanoparticles (B) to the binder (A) is from 1:2 to 1:1; curing the composition at a temperature of 85°C to 150°C; and forming a wavelength conversion layer on the reflective layer; Wherein, the reflective layer is thermally stable at a working temperature of 250°C.

11. The method according to claim 10, wherein: The composition has a viscosity of up to 1500 centipoise (cP).

12. The method according to claim 10, wherein: The composition is applied by dispensing, spraying, brushing, flowing, coating or screen printing.

13. The method according to claim 10, further comprising: Before applying the composition to the substrate, the surface of the reflective titanium dioxide (TiO2) nanoparticles (B) is modified with the organic alcohol, the siloxane, aluminum oxide (Al2O3), zirconium dioxide (ZrO2) or silicon dioxide (SiO2).

14. The method according to claim 10, further comprising: The composition is formed by the following steps: The reflective titanium dioxide (TiO2) nanoparticles (B) are mixed with the binder (A) to form a mixture, and The mixture is refrigerated to form the composition before applying the composition onto the substrate to form the reflective layer.

Citation Information

Patent Citations

  • Nitride semiconductor light-emitting device

    CN103503182A

  • Wavelength conversion device and production method thereof as well as related light-emitting device

    CN104100933A

  • Wavelength conversion device and related light emitting device thereof

    CN105322433A

  • Hybrid material for use as coating means in optoelectronic components

    CN106661272A

  • Enhancement mode wavelength conversion equipment

    CN205721046U